THE IMPORTANCE OF NATIONAL MOVEMENT GAMES IN THE PHYSICAL DEVELOPMENT OF YOUTH - M. Tashbaeva (Journal Park Publishing, 2022)
This article highlights the important aspects of the national movement folk games in keeping young people physically active and healthy in all respects.
Keywords: physical education; national movement game; speed